1996
DOI: 10.1029/96jb01209
|View full text |Cite
|
Sign up to set email alerts
|

Recent tectonic, magmatic, and hydrothermal activity on the East Pacific Rise between 17°S and 19°S: Submersible observations

Abstract: The objective of the Naudur cruise (December 1993) of the submersible Nautile was to study the interaction among magmatic, tectonic, and hydrothermal processes at a very fast spreading mid‐ocean ridge axis. Twenty‐three dives were completed, both along and across the axis, in four areas located between 17°10′ and 18°45′S on the East Pacific Rise. Rock, sulfides, water, and biological samples have been collected along each of the segments. Two main types of segments have been distinguished, characterized either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 26 publications
4
75
1
Order By: Relevance
“…[36] The Lucky Strike lava lake contains flat lavas and lava pillars similar to those observed at the axis of the intermediate and fast spreading ridges [Ballard, 1979;Francheteau et al, 1979;Auzende et al, 1996;Gregg and Chadwick, 1996;Gregg et al, 2000;Lagabrielle et al, 2001;Chadwick, 2003;Tanaka et al, 2007]. Lava pillars have also been reported at the Mid-Atlantic Ridge south of the Oceanographer transform [Bideau et al, 1998].…”
Section: Lucky Strike Lava Lakementioning
confidence: 86%
“…[36] The Lucky Strike lava lake contains flat lavas and lava pillars similar to those observed at the axis of the intermediate and fast spreading ridges [Ballard, 1979;Francheteau et al, 1979;Auzende et al, 1996;Gregg and Chadwick, 1996;Gregg et al, 2000;Lagabrielle et al, 2001;Chadwick, 2003;Tanaka et al, 2007]. Lava pillars have also been reported at the Mid-Atlantic Ridge south of the Oceanographer transform [Bideau et al, 1998].…”
Section: Lucky Strike Lava Lakementioning
confidence: 86%
“…comm.). The Oasis field is located on a lava flow that had 'young' characteristics in 1993; large areas of diffuse discharge without sessile animals and with a turbid, flocculent appearance (Fouquet et al 1994, Auzende et al 1996. The Oasis field corresponds to the northern 'L0' region of the Embley et al (1998) study, where, in 1995, 'Shinkai 6500' divers observed colonization of small, low-effusion-rate vents in what had been described as 'uncolonized areas of shimmering water' by 'Nautile' divers the previous year (Fouquet et al 1994).…”
Section: Site Descriptionsmentioning
confidence: 99%
“…This area has been extensively mapped [Scheirer et al, 1996], and was the focus of two submersible dive programs [Renard et al, 1985;Auzende et al, 1996], a detailed seismic refraction/reflection survey (TERA) , and the Mantle ELectromagnetic and Tomographic (MELT)…”
Section: The Study Areamentioning
confidence: 99%